2016
DOI: 10.1021/acs.langmuir.6b02342
|View full text |Cite
|
Sign up to set email alerts
|

Influence of csgD and ompR on Nanomechanics, Adhesion Forces, and Curli Properties of E. coli

Abstract: Curli are bacterial appendages involved in the adhesion of cells to surfaces; their synthesis is regulated by many genes such as csgD and ompR. The expression of the two curli subunits (CsgA and CsgB) in Escherichia coli (E. coli) is regulated by CsgD; at the same time, csgD transcription is under the control of OmpR. Therefore, both genes are involved in the control of curli production. In this work, we elucidated the role of these genes in the nanomechanical and adhesive properties of E. coli MG1655 (a labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
(192 reference statements)
0
8
0
Order By: Relevance
“…It should be noted that previous studies have found that the pT7-CsgD plasmid induces biofilm production in E. coli K-12 at least as well as the ompR234 allele (28,31,43). Overexpression of curli in MC4100 via pT7-CsgD permitted pellicle formation in shaking conditions despite lack of motility, although pellicle formation was severely hindered when compared to PHL644 (motile) and PHL644h (hypermotile).…”
Section: Curli Overproduction In Nonmotile Mc4100mentioning
confidence: 93%
See 1 more Smart Citation
“…It should be noted that previous studies have found that the pT7-CsgD plasmid induces biofilm production in E. coli K-12 at least as well as the ompR234 allele (28,31,43). Overexpression of curli in MC4100 via pT7-CsgD permitted pellicle formation in shaking conditions despite lack of motility, although pellicle formation was severely hindered when compared to PHL644 (motile) and PHL644h (hypermotile).…”
Section: Curli Overproduction In Nonmotile Mc4100mentioning
confidence: 93%
“…Initial work focused on generating a robust, recombinant Escherichia coli K-12 biofilm capable of biocatalysis (29,30,31). We grew a biofilm-forming strain of E. coli K-12, PHL644, a variant of MC4100 with a mutation in the ompR gene (ompR234) resulting in increased curli expression (23), in conditions conducive to biofilm formation (M63+ minimal medium, 30 °C, and orbital shaking at 70 rpm).…”
Section: E Coli K-12 Forms Pelliclesmentioning
confidence: 99%
“…Our future studies will also include an examination of the anti-sigma factor FlgM, a small protein that binds to FliA, inhibiting FliA binding to DNA, and its role in creating negative feedback loops that might be tempering the overexpression response of FliA (Park et al, 2001;Barembruch and Hengge, 2007). FlgM expression is induced by FliA and is inhibited by CsgD, a transcriptional regulator that has its own transcription regulated by OmpR, a protein that is constitutively active in PHL628 cells (Dudin et al, 2014;Perni et al, 2016). This complex network of interactions could explain both the tempered nature of our CLSM and biochemical results, despite exogenous overexpression of FliA.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical Characterization: Young's modulus measurements of the ME membranes were carried out through nanoindentation according to a published method by Polina Prokopovich et.al. [33] Briefly, an atomic force microscope (AFM, XE-100, Park Systems, South Korea) was employed for adhesion force measurements using a cantilever (Veeco, ORC8-10, tip radius of 15 nm, nominal spring constant K cantilever of 0.05 Nm -1 ). Therefore, Young's modulus of the samples was calculated by following the formula:…”
Section: Fabrication Of Me Membrane-ferrule Assemblymentioning
confidence: 99%